The sedimentary history of the inner‐alpine Inn Valley, Austria: extending the Baumkirchen type section further back in time with new drilling. (January 2017) - Barrett, Samuel; Starnberger, Reinhard; Tjallingii, Rik; Brauer, Achim; Spötl, Christoph
ABSTRACT: The Baumkirchen clay pit near Innsbruck, western Austria, is a well‐known site in Alpine Quaternary stratigraphy. Lacustrine sediments from the last glacial cycle from within the Alps provide a unique opportunity to investigate the regional palaeoclimate. Recent drilling has extended the known sequence to a total length of at least 250 m consisting of almost entirely well‐laminated clayey silt. Luminescence dating identified two lake sequences, separated by a hiatus of ca. 7000–15 000 years. Lake phase 1 spans the period ca. 77–55 ka, i.e. from about Marine Isotope Stage (MIS) 5/4 to the MIS 4/3 transition. Lake phase 2 extends from mid‐ to late MIS 3 between ca. 45 and 33 ka. Down‐core X‐ray fluorescence core scanning confirmed the presence of the lake phases in the sediment composition, suggesting different sediment sources and/or transport mechanisms during these two intervals. A unique section of exotic, angular, silt matrix‐supported gravel at the top of lake phase 1 is interpreted as ice‐rafted debris. Luminescence dating constrains this layer to ca. 55 ka, thus providing the first evidence of a late MIS 4 or early MIS 3 ice advance confined to the interior of the Eastern Alps. A conceptual model of the sedimentary history of the valley is presented.